Taxonomy of the Oriental leafhopper genus Parabolopona (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) with a new species from China - Xu, Deliang; Zhang, Yalin (Zootaxa, 2020)
The Oriental leafhopper genus Parabolopona Matsumura (Cicadellidae: Deltocephalinae: Drabescini: Paraboloponina) is reviewed with description of a new species, Parabolopona yunnanensis sp. nov., from China. An updated checklist with distributions and a key to males of this genus are also provided.